2018
DOI: 10.1136/jim-2017-000494
|View full text |Cite
|
Sign up to set email alerts
|

Airway Transplantation of Adipose Stem Cells Protects against Bleomycin-Induced Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive interstitial lung disease with poor prognosis. Adipose-derived stem cells (ADSC) have demonstrated regenerative properties in several tissues. The hypothesis of this study was that airway transplantation of ADSC could protect against bleomycin (BLM)-induced pulmonary fibrosis (PF). Fifty-eight lungs from 29 male Sprague-Dawley rats were analyzed. Animals were randomly divided into five groups: a) control (n=3); b) sham (n=6); c) BLM (n=6); d) BLM+ADSC-2d (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Adipose tissue-derived stromal cells (ASCs) have been tested experimentally for the treatment of various conditions, including IPF ( Barczyk et al, 2015 ). A variety of studies showed attenuated, but not resolved, fibrosis after ASC treatment in bleomycin-induced lung fibrosis in mice and rats ( Lee et al, 2014 ; Jiang et al, 2015 ; Tashiro et al, 2015 ; Rathinasabapathy et al, 2016 ; Reddy et al, 2016 ; Llontop et al, 2018 ; Felix et al, 2020 ). Similar results were achieved in other rat models of pulmonary fibrosis ( Fikry et al, 2015 ; Chen et al, 2018 ; Zhang et al, 2019 ; Radwan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue-derived stromal cells (ASCs) have been tested experimentally for the treatment of various conditions, including IPF ( Barczyk et al, 2015 ). A variety of studies showed attenuated, but not resolved, fibrosis after ASC treatment in bleomycin-induced lung fibrosis in mice and rats ( Lee et al, 2014 ; Jiang et al, 2015 ; Tashiro et al, 2015 ; Rathinasabapathy et al, 2016 ; Reddy et al, 2016 ; Llontop et al, 2018 ; Felix et al, 2020 ). Similar results were achieved in other rat models of pulmonary fibrosis ( Fikry et al, 2015 ; Chen et al, 2018 ; Zhang et al, 2019 ; Radwan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Grading was scored on a scale from 0 to 8, using the average of microscope field scores [ 44 ]. Seventeen of them showed that the Ashcroft scoring were significantly lower in the MSCs treatment group than that in the BLM group (all p < 0.05) [ 11 15 , 18 21 , 23 , 29 , 30 , 32 , 33 , 41 – 43 ]. Three studies found no significant difference in the Ashcroft score between the MSCs and the BLM groups [ 22 , 28 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both the early and delayed treatment groups showed significant reductions in lung inflammation, collagen deposition, and Ashcroft score. Although lung function in the delayed treatment group was not complete restored [ 11 , 15 , 29 ]. Four studies found that the early treatment group (day 0 or 1) had significantly reduced PF score and collagen content, while the delayed treatment group (day 7 or 9) had no significant difference in the degree of PF compared with the BLM group [ 18 , 31 , 38 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Groups ii and iii mice were anesthetized with 2.5% tribromoethanol (0.8% NaCl, 1 mM Tris (pH 7.4), 0.25 mM EDTA (pH 7.4)) and administered 3.5 mg/kg bleomycin solution (Sigma B5507-15un) in 50 μ L of phosphate-buffered saline (PBS) intratracheally on day 0 using a 1 mL syringe with a 25G needle. Control animals were treated with PBS instead of BLM [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%